Método para acompanhamento de fases em um aço inoxidável duplex pela análise do ruído de Barkhausen e do primeiro harmônico - Silva, João Batista de Oliveira (2024)
Non-destructive electromagnetic tests based on Barkhausen magnetic noise analysis have been developed for analysis of residual stresses, heat treatment effects, monitoring of microstructures harmful to toughness, among other conditions. This noise is generated by the interaction between the movement of the magnetic domains walls and the microstructures of the material. Microstructures harmful to the tenacity of duplex stainless steels, such as the sigma phase, can have their formation accompanied by these tests, as these are paramagnetic and their formation lead to changes in the permeability of the material, allowing them to be detected by the analysis of Barkhausen magnetic noise In the present work, a study of the characteristics of emitting waves was carried out, through the analysis of the Barkhausen magnetic noise, variations in the amplitudes of the first harmonic of the main wave and the material thickness, in order to monitor the formation of the sigma phase, in an SAE 2205 steel supplied as laminate. In this case, the receiving coil is replaced by a Hall effect sensor, in order to simplify the test and facilitate its standardization. Sinusoidal emission waves with frequencies from 5 Hz to 50 Hz and with amplitudes ranging from 0.25 V to 9 V were applied to samples with thicknesses of 2 mm, 4 mm, 6 mm and 8 mm with different amounts of sigma phase of 5 %, 17 % e 18,8 %. The results show that the best work region consists of the application of waves with amplitudes from 1 V to 2 V, for all frequencies, and the best ones were obtained with the variation in the amplitudes of the harmonics of the main wave. The study of the variation in thickness shows that the behavior of the variation in the root mean square of the signal has an inverse behavior for thicknesses of 2 mm and 8 mm, with a transition in behavior for thicknesses of 4 mm and 6 mm. Thus, the test proved to be sensitive to microstructural variations and effective for monitoring the formation of the deleterious sigma phase.